Assessing the translation of diagnostic colorectal cancer biomarkers from bench to bedside - Baggaley, Alice E.; Kabbani, Jade; Savva, Katerina Vanessa; Gogoi, Prerana; Kinross, James M.; Ni, Melody Zhifang; Peters, Christopher J. (Frontiers in Medicine, 2025)
BackgroundColorectal cancer is the second leading cause of cancer mortality worldwide. Evidence demonstrates that screening identifies patients with earlier disease to improve survival. It is imperative that diagnostic biomarkers are efficiently translated to clinical practice.AimWe aimed to assess the state of biomarker translation by comparing the number of diagnostic colorectal cancer biomarkers in clinical use (successful) with the total number of discovered diagnostic colorectal cancer biomarkers not yet clinically useful (stalled).MethodA literature search identified all published diagnostic colorectal cancer biomarkers. Data was extracted from eligible papers including biomarker name, authors, journal and impact factor, and publication date. Guidelines from national and international authorities/groups were searched and a clinical expert consulted to identify successful diagnostic colorectal cancer biomarkers. Outcomes included number of stalled and successful diagnostic colorectal cancer biomarkers discovered in the literature, number of publications for each biomarker and their highest journal impact factor.ResultsAfter screening >32,000 papers, 2,910 diagnostic colorectal cancer biomarkers were identified. Of these, four were approved for use in patient care at the time of review, representing a translation rate of just 0.14%. Successful biomarkers were found to have a higher publication frequency, and higher journal impact factor when compared to stalled biomarkers.ConclusionThis study demonstrates a profoundly low rate of translation of diagnostic colorectal cancer biomarkers and identifies the huge translation gap within this field. 84% of biomarkers have only one published paper, suggesting a lack of progression toward approval and commercialisation. There is great scope for improved biomarker translation.